Multiplexity and strategic alliances: The relational embeddedness of coalitions in social movement organisational fields - Simpson, C (Elsevier, 2015)
While scholars have embraced the notion of social movements as networks, there has been little empirical exploration of the emergence of coalitions within these multilayered systems. Here I explore the role of overlapping relations in alliance formation amongst a group of 55 health-related professional social movement organisations mobilised against austerity. Using cross-sectional bivariate exponential random graph models, I find dependencies between digital proxies for alliance, shared allies, information exchange, positive nomination and offline colobbying activity at the dyadic, degree and triadic levels. Cross-network associations indicate that multiplexity plays a non-trivial role in the formation of alliances and, more generally, social movement organisational fields, necessitating increased attention from scholars of social movements.